Neurohormonal Activation After Atrial Fibrillation Initiation in Patients Eligible for Catheter Ablation: A Randomized Controlled Study - Emmanouil Charitakis; Håkan Walfridsson; Eva Nylander; Urban Alehagen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Biomarker activation in atrial fibrillation (AF) has been widely studied, but the immediate effect of AF initiation remains unclear. We studied the effect of AF initiation on 2 cardiac biomarkers: the N‐terminal fragment of the proB‐type natriuretic peptide (NT‐proBNP), the midregional fragment of the N‐terminal of pro‐atrial natriuretic peptide (MR‐proANP), and 2 extracardiac biomarkers—the copeptin and the midregional portion of proadrenomedullin (MR‐proADM). Methods and Results This was a randomized controlled study, including 45 patients with AF who had been referred for radiofrequency ablation to the University Hospital, Linköping, Sweden, between February 2012 and April 2014. Freedom from AF during the 4 days prior to radiofrequency ablation was confirmed by transtelephonic ECGs. Biomarkers were collected from the femoral vein (fv), coronary sinus (CS), and left atrium (LA) prior to AF initiation (baseline) and 30 minutes later. The MR‐proANP and NT‐proBNP concentrations increased in the intervention group compared with the control group 30 minutes after the initiation of AF (MR‐proANP: Pfv<0.001, PCS<0.001, PLA<0.001; NT‐proBNP: PLA<0.001). Copeptin levels in patients without ischemic heart disease were decreased after the initiation of AF (Pfv=0.003, PCS=0.015, PLA=0.011). Conclusions AF is a strong stimulus that results in immediate activation of different biomarkers. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT01553045.